Review of A complete guide to Antarctic wildlife: birds and mammals of the Antarctic Continent and the Southern Ocean, by Hadoram Shirihai - Mehlum, Fridtjof (Polar Research, 2012)
This impressive book is an invaluable, fully illustrated, wildlife guide for tourists and scientists visiting the Southern Ocean and Antarctica.
Keywords: Antarktis; Sørishavet; bokanmeldelser; dyreliv; fugler; marin biologi; ornitologi; pattedyr; zoologi

Antarktis : en eventyrlig seilas - Aasheim, Stein P; Nævra, Arne (NRK aktivum, 2007)
Keywords: Antarktis; dyreliv; geografi; historie; hvalfangst; populærvitenskap; reisebeskrivelser

Miljøgifter og radioaktivitet i norsk fauna : inkludert Arktis og Antarktis - Knutzen, Jon; Fjeld, Eirik; Hylland, Ketil; Killie, Barbro; Kleivane, Lars; Lie, Elisabeth; Nygård, Torgeir; Savinova, Tatiana; Skåre, Janneche Utne; Aanes, Karl Jan (Direktoratet for naturforvaltning, 1999)
Keywords: Antarktis; dyreliv; forurensning; miljøgifter; polarområdene; radioaktivitet; toksikologi; zoologi

Virkninger av klimaendringer i polarområdene : bidrag til den interdepartementale klimautredningen - Kverndal, Arnt-Ivar; Elvebakk, Arve; Jaworowski, Zbygniew; Hansson, Rasmus (Norsk Polarinstitutt, 1990)
Keywords: Antarktis; biologi; drivhuseffekten; dyreliv; fiskeri; flora; havbruksnæring; havis; havnivå; isbreer; klimaendringer; klimagasser; permafrost; planter; polarområdene; vannressurser; økologi

Food Consumption of Seals in the Antarctic Pack Ice - Øritsland, Torger (Smithsonian Institution, 1977)
Keywords: Antarktis; biologi; dyreliv; havis; seler; sjøis; zoologi

Studies on the southern stocks of Blue and Fin whales - Jonsgård, Åge; Ruud, Johan T (Hermann, 1964)
Keywords: Sørishavet; biologi; dyreliv; hvaler; hvalfangst; marinbiologi

Trekk av Sydishavets dyreliv - Olstad, Ola (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1928)
Keywords: Antarktis; Bouvetøya; Lars Christensen; Norvegia ekspedisjoner; Peter I. Øy; dyreliv; forskning; zoologi